Barrier diagram (Bow Tie) quality issues for operating managers. Issue 4 (27th January 2014) - Pitblado, Robin; Weijand, Pieter
<x xml:space="preserve">Abstract</x> The Oil & Gas (O&G) and petrochemical industries have been much more successful at reducing occupational safety events as compared to major process accidents over the past 20 years. A novel approach based on barrier diagrams, called Bow Ties, directly addresses major accidents and the focus on barriers and maintaining barrier functions has been shown to be effective in O&G operations in the North Sea. While not mandated in OSHA 1910.119, many companies are starting to apply barrier methods to improve operations and reduce major accidents. The Bow Tie approach is deceptively simple and many errors are made in Bow Tie diagrams. This is due to a lack of a formal standard or accepted methodology for the approach. This article describes many common errors that appear in Bow Ties used for operational safety and how these might be rectified. Since Operating Managers will rely on these risk diagrams as a key part of their process safety program, it is essential that they have good quality and not contain structural errors. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 355–361, 2014